The Use of Numbered Heads Together to Improve The 10th Grade Students’ Reading Comprehension Achievement At Man 2 Lamongan - Ahmad Fauzi; Getari Adyagarini; Mas Khasila Imani; Titis Setia Yanti; Ulfa Vadhila; Syaikhul Hadi (IJET (Indonesian Journal of English Teaching), 2020)
Among four language skills which are listening, reading, speaking and writing, reading is one of the most significant skills to be mastered by students in all grades. Reading gives students immense input of knowledge and information through various texts. Nonetheless, in the classroom, reading activities are long considered as monotonous and not interesting. Therefore, it becomes an urge for the teachers to apply more interesting technique to teach reading. In response to that matter, the teacher can use Numbered Heads Together technique as an alternative technique in teaching reading. This study explores the implementation of Numbered Heads Together in teaching descriptive text and describe the students’ reading comprehension in the implementation of Numbered Heads Together. The subject of this study were students tenth graders of MAN 2 Lamongan. This study is a qualitative case study which was conducted in two meetings. In the first meeting, the teacher just taught the descriptive text without any techniques. In the next meeting, the teacher introduced the technique and applied it in the class. The data of this study were collected from the result of the students’ task. The result of this study shows that the implementation of Numbered Heads Together assisted the students to engage actively in the whole process of learning. After using this technique, the number of students who got good achievement increased. It means that the students’ reading comprehension is improved after the implementation of NHT. In conclusion, NHT is a good technique to be used in teaching descriptive text, especially for the tenth grade students, since it helps them to overcome their difficulties in reading, creates a positive atmosphere in the class, and builds a good interaction for both the teachers and students. Keywords: numbered heads together, descriptive text, reading.